Programming living sensors for environment, health and biomanufacturing. Issue 6 (7th May 2021) - Wan, Xinyi; Saltepe, Behide; Yu, Luyang; Wang, Baojun
Summary: Synthetic biology offers new tools and capabilities of engineering cells with desired functions for example as new biosensing platforms leveraging engineered microbes. In the last two decades, bacterial cells have been programmed to sense and respond to various input cues for versatile purposes including environmental monitoring, disease diagnosis and adaptive biomanufacturing. Despite demonstrated proof‐of‐concept success in the laboratory, the real‐world applications of microbial sensors have been restricted due to certain technical and societal limitations. Yet, most limitations can be addressed by new technological developments in synthetic biology such as circuit design, biocontainment and machine learning. Here, we summarize the latest advances in synthetic biology and discuss how they could accelerate the development, enhance the performance and address the present limitations of microbial sensors to facilitate their use in the field. We view that programmable living sensors are promising sensing platforms to achieve sustainable, affordable and easy‐to‐use on‐site detection in diverse settings. Abstract : Synthetic biology offers new tools and capabilities of engineering microbes with defined functions as new biosensing platforms for environmental monitoring, disease diagnosis and adaptive biomanufacturing. Here, we summarize the latest advances in synthetic biology and discuss how they could accelerate the development, enhance the performance and address the present limitations of microbial sensors to facilitate their use in the field. We view that programmable living sensors are promising sensing platforms to achieve sustainable, affordable, and easy‐to‐use on‐site detection in diverse settings.